Outcomes of nutrition status assessment by bhumibol nutrition triage/nutrition triage (BNT/NT) in multicenter THAI-SICU study - Kaweesak Chittawatanarat (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: The objective of the study is to evaluate the nutrition assessment tool used by Bhumibol Nutrition Triage/Nutrition Triage (BNT/NT) for patient outcomes in a surgical intensive care unit (SICU). Material and Method: All data were retrieved from the THAI-SICU database. A total of 1,685 patients from three medical centers were participants in the nutrition project and were enrolled onto this study. The parameters needed for BNT/NT scoring were recorded including body mass index (BMI), weight change, energy delivery, age, and disease severity. The BNT/ NT calculation was classified into 4 groups as BNT/NT I to IV. An adjusted odds ratio (OR) with 95% confidence interval (CI) of mortality and sepsis occurrence were reported. Results were classed as being statistically significant at p<0.05. Results: Regarding the nutrition assessment classification, the patients admitted to SICU were classified as BNT/NT class I48.6%, class II 30.0%, class III 9.3%, and class IV 12.1%. There were statistically significant differences between classes in terms of BMI, weight change, energy delivery and disease severity. In addition, the BNT/NT classification was also significantly associated with ICU mortality [OR (95% CI): 1.51 (1.25-1.83); p<0.001], 28 day mortality [1.47 (1.23-1.74); p<0.001], and sepsis occurrence [1.41 (1.25-1.60); p<0.001]. Conclusion: Most of the patients admitted to SICU had a low nutrition risk BNT/NT class I and II. The higher BNT/NT scores were associated with mortality and sepsis occurrence in SICU.